Development of Natural Tourist Attractions of Kobo Kecil Village Molimpungan Waterfalls - Monoarfa, Lindawati; Munawir, Abdillah (ASTONJADRO, 2024)
Kotamobagu City is a service city where most of its income is obtained from trade, hotel, health and other services. As a service city, it is necessary to develop existing potentials, for example in terms of tourism which is generally found in every region, in which case there is potential. One of the tourist attractions is in Kobo Kecil Village, South Kotamobagu District, Kotamobagu City in the form of the Molimpungan Waterfall natural tourist attraction which requires redevelopment so that it can have an impact on the economy of the surrounding community and Kotamobagu City in general. The research method used is qualitative descriptive analysis, with SWOT analysis techniques. The results of the research explain that the City of Services, by developing tourism potential, apart from having an impact on the surrounding economy and society in general, can also contribute to local original income. By developing this tourist attraction, it can encourage the surrounding community to be more creative and active so that it can encourage the opening of new employment opportunities and encourage improving the economy of communities around tourist attractions and increasing opportunities for both small and medium businesses. The emergence of new jobs and business opportunities can increase community income and local revenue so that it can finance the development of existing facilities and infrastructure at the Molimpungan Waterfall natural tourist attraction.